Marine Renewable Energy for Island Integrated Energy Systems Optimisation: A Review - Wen Zhao; Bohong Wang; Hengcong Tao (Chemical Engineering Transactions)
Combining marine renewable energy with traditional energy and rationally constructing an integrated island energy system is crucial to alleviating island energy supply problems and the clean transformation of coastal energy. This paper analyses the energy demand characteristics of different types of energy islands to introduce existing optimisation models and technologies for island integrated energy systems. The current solutions and their advantages and disadvantages from the perspectives of modelling methods and system simulation are discussed, with future research directions proposed to guide sustainable energy development in island regions. Integrated energy systems can enhance energy utilisation efficiency and promote the integration of renewable energy, this paper aims to inspire readers to develop new functionalities and modules based on existing technologies, providing valuable references and insights for sustainable energy development in island regions.